2013
DOI: 10.1089/jmf.2012.2558
|View full text |Cite
|
Sign up to set email alerts
|

Chlorophyll-Related Compounds Inhibit Cell Adhesion and Inflammation in Human Aortic Cells

Abstract: The objectives of this study were to investigate the effects of chlorophyll-related compounds (CRCs) and chlorophyll (Chl) a + b on inflammation in human aortic endothelial cells. Adhesion molecule expression and interleukin (IL)-8, nuclear factor (NF)-jB p65 protein, and NF-jB and activator protein (AP)-1 DNA binding were assessed. The effects of CRCs on inflammatory signaling pathways of signal transducers and activators of transcription 3 (STAT3) and mothers against decapentaplegic homolog 4, respectively i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 55 publications
0
3
0
Order By: Relevance
“…Chlorophyll-related compounds have been shown to have antioxidative capacities and anti-inflammatory activities [26][27][28] . Moreover, Lin et al showed, in vitro, that chlorophyll-related compounds inhibit TNF-α-induced monocyteendothelial cell adhesion, vascular cell adhesion molecule-1, intercellular adhesion molecule-1, IL-8 and NF-κB expression in human aortic smooth muscle cells 29 .These results highlight the close link between the microbiome, metabolomic changes and inflammation.…”
Section: Discussionmentioning
confidence: 93%
“…Chlorophyll-related compounds have been shown to have antioxidative capacities and anti-inflammatory activities [26][27][28] . Moreover, Lin et al showed, in vitro, that chlorophyll-related compounds inhibit TNF-α-induced monocyteendothelial cell adhesion, vascular cell adhesion molecule-1, intercellular adhesion molecule-1, IL-8 and NF-κB expression in human aortic smooth muscle cells 29 .These results highlight the close link between the microbiome, metabolomic changes and inflammation.…”
Section: Discussionmentioning
confidence: 93%
“…Chlorophyll and its derivatives and metabolites are believed to have antioxidant, anti-inflammatory, and antiviral properties. Eating foods with a high content of these dyes may have a beneficial effect on health [47,[51][52][53][54][55][56][57][58][59][60]. For example, the phyllobilins (e.g., phylloucobilin, dioxobilin-type phylloucobilin, and phylloxanthobilin) are natural products of chlorophyll degradation.…”
Section: Chlorophyllsmentioning
confidence: 99%
“…The results of Lauritano et al's [56] experiments also showed that the products of the metabolic degradation of chlorophyll can inhibit the secretion of tumor necrosis factor alpha (TNF-α) using lipopolysaccharide (LPS)-stimulated macrophages. Also, Lin et al [57] observed the anti-inflammatory effect of chlorophyll and its derivatives by reducing the synthesis of proinflammatory factors and reducing the adhesion of inflammatory cells to the aortic endothelium in a mechanism dependent on the secretion of TNF-α by monocytes. Wang et al [58], based on the results of their own research, postulate that chlorophylls can be a natural means of increasing the effectiveness of chemotherapeutic agents in the case of multi-drug-resistant pathogens.…”
Section: Chlorophyllsmentioning
confidence: 99%